FACTORS INFLUENCING URINARY TRACT INFECTIONS PRACTICES AMONG MALE AND FEMALE PATIENTS IN WASIT HOSPITALS, IRAQ - Rasool J. Saad; Wasen A. Farid; Abeer Al-Sawafi (International Journal Multidisciplinary (IJMI), 2026)
Objective: Urinary tract infections (UTIs) remain a significant global health challenge, requiring a deep understanding of preventive practices for patients to reduce recurrence. The study aimed to identify the key socio-demographics and the factors influencing practices related to UTIs among patients in Wasit hospitals, Iraq. Method: A descriptive cross-sectional study with 350 participants using non-random, convenience sampling. It was carried out at Al-Zahraa and Al-Karama Teaching Hospitals in Wasit Governorate, Iraq. Practice levels were categorized based on scores: Poor (<50%), Fair (50%–75%), and Good (≥75%). Results: A total of 350 patients, the sex ratio is 66.9% female to 33.1% male. Although this study discovered that 56.0% of patients have a good practice score for UTIs, a large proportion of patients (57.1%) have a history of recurrent infections. This study found a statistically significant correlation between practice scores with sex, educational level, employment status, and socioeconomic status (SES) at P < 0.001. Novelty: In this study, more than half of the patients avoid taking antibiotics directly without a prescription. This study clarifies that male sex, high education, high professional occupation, and high SES have good assessment scores for practices about UTI. Also, it clarifies that men have better prevention practices than women.